PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO SURYA ABADI VAPESTORE DI SITUBONDO - Seinuri, Seinuri; Sari, Lita Permata; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2023)
Marketing is one of the main activities carried out by e-cigarette companies, which has become a new phenomenon among young people in Situbondo. Technological developments are increasingly advanced, recently we know that electric cigarettes have started to be in demand by the public, especially in lifestyle developments among men. Currently, men and women, especially young people, are busy using electric cigarettes. E-cigarettes or commonly called vape. The population in this study are consumers of the Surya Abadi Vapestore Store in Situbondo. The sampling technique is determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that product quality has a significant positive effect on consumer trust, promotion has a significant positive effect on consumer trust, product quality has a significant positive effect on purchasing decisions, promotion has a positive but not significant effect on purchasing decisions, trust consumers have a significant positive effect on purchasing decisions, product quality on purchasing decisions through consumer trust has a significant positive effect, promotions on purchasing decisions through consumer trust have a significant positive effect.